“Efecto de la inversión extranjera directa en el consumo de energía renovable para 18 países de América Latina durante el periodo de 1990-2017” - Jiménez Cumbicus, Edwin Enrique (2021)
Renewable energy consumption (REC) worldwide represents only 10.8% of total energy compared to non-renewable energy consumption (NREC) which is more than 70%. In this sense, the research focuses on evaluating the relationship between foreign direct investment (FDI) and renewable energy consumption in 18 Latin American countries during the period 1990-2017. The data used come from the International Energy Agency database (IEA, 2020) and the World Bank database (WDI, 2020). The methodology applied is based on a Generalized Least Squares (GLS) econometric model, the Westerlun test (2007) to determine if there is cointegration in the long run and the Granger test (2008) to establish if there is causality. The main results obtained show that CER and FDI have a decreasing trend and a negative correlation. Cointegration tests showed the existence of cointegration in the long run between FDI and CER in Latin America. The causality tests indicated that there is unidirectional causality for Latin American countries and PIA. In terms of policy implications, governments should implement fiscal policies that encourage the entry of foreign companies to increase the use of green technologies and help boost projects in the renewable energy sector.